The Test for Creative Thinking: An authentic tool for art education to assess creativity through visual expression. Issue 1 (1st March 2013) - Kárpáti, Andrea; Gyebnár, Viktória
This article introduces a creativity test, an authentic and flexible assessment instrument that invites participants to create a meaningful image out of a set of visual signs. The elements offered for completion, repetition, modification, inclusion and composition are not culturally biased and invite the use of a variety of drawing styles. This test has been successfully used by art educators to identify talented students for enrolment in special courses and also by teachers who want to know more about the creative potentials of students who are verbally less fluent and therefore are not successful at school. In this article, we discuss the general findings of the Test for Creative Thinking/Drawing Production (TCT/DP) that was administered between 2000 and 2010 to 1050 children and young people aged 7-18 years during the course of the national standardization of this instrument. We compare two generally known and often discussed models of visual skills development created by Victor Lowenfeld, Howard Gardner, Ellen Winner and Jessica Davis in relation to the test results obtained from a comparison of Hungarian and German children. We focus on important issues of art education: cognitive growth manifest in visual language use, the issue of the 'drawing gap' in adolescence and the use or uselessness of developmental stages in relation to artistic performance.